2017
DOI: 10.1038/s41598-017-03687-9
|View full text |Cite
|
Sign up to set email alerts
|

RNAseq based transcriptomics study of SMCs from carotid atherosclerotic plaque: BMP2 and IDs proteins are crucial regulators of plaque stability

Abstract: Carotid artery atherosclerosis is a risk factor to develop cerebrovascular disease. Atheroma plaque can become instable and provoke a cerebrovascular event or else remain stable as asymptomatic type. The exact mechanism involved in plaque destabilization is not known but includes among other events smooth muscle cell (SMC) differentiation. The goal of this study was to perform thorough analysis of gene expression differences in SMCs isolated from carotid symptomatic versus asymptomatic plaques. Comparative tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 78 publications
1
19
0
Order By: Relevance
“…In a recent study, VSMCs isolated from carotid atherosclerotic plaques were found to express a series of macrophage markers [ 14 ], concomitant with a macrophage-like phenotype [ 25 ]. Analysis of the expression levels of CD68 and LGALS3 showed that both macrophage markers were significantly augmented in PLQ compared to MIT-VSMCs ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, VSMCs isolated from carotid atherosclerotic plaques were found to express a series of macrophage markers [ 14 ], concomitant with a macrophage-like phenotype [ 25 ]. Analysis of the expression levels of CD68 and LGALS3 showed that both macrophage markers were significantly augmented in PLQ compared to MIT-VSMCs ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…Cell density at harvest was 200,000 cells/5 mL in a T25 flask. All experiments were carried out with cells in passage zero in order to keep overall cell characteristics as similar as possible to those in the natural context, and to avoid extended cultivation periods which would influence the expression levels of analyzed genes [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The upregulated expression of ITGAM is found in the middle cerebral occlusion brain of rat [40]. ID3 regulates many biological processes, including cell growth, apoptosis, senescence, and angiogenesis [41]. Doran et al [42] found that ID3 was a key atheroprotective transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted with an RNeasy Mini Kit (Qiagen Inc. Germantown, MD 20874) and analyzed by RNAseq. 32 …”
Section: Methodsmentioning
confidence: 99%